Phytohormone profiling in relation to osmotic adjustment in NaCl-treated plants of the halophyte tomato wild relative species Solanum chilense comparatively to the cultivated glycophyte Solanum lycopersicum. (May 2017) - Gharbi, Emna; Martínez, Juan-Pablo; Benahmed, Hela; Hichri, Imène; Dobrev, Petre I.; Motyka, Václav; Quinet, Muriel; Lutts, Stanley
Highlights: Hormonal profiling was established in the glycophyte Solanum lycopersicum and halophyte Solanum chilense . Concentration of most hormonal compounds were higher in Solanum chilense than in Solanum lycopersicum . Na + and K + ions were the major contributors to osmotic adjustment in the halophyte Solanum chilense . Phytohormones may be involved in the capacity of Solanum chilense to use inorganic ions as osmotica. Abstract: A holistic approach was used to investigate the hormonal profile in relation with osmotic adjustment under salinity in Solanum lycopersicum and its halophyte wild relative Solanum chilense . Plants were subjected to 125 mM NaCl for 7 days. Solanum chilense displayed a contrasting behaviour comparatively to S. lycopersicum, not only for mineral nutrition, but also regarding the modalities of osmotic adjustment and phytohormonal profiling. The extent of osmotic adjustment was higher in S. chilense than in S. lycopersicum. Ions K + and Na + were the major contributors of osmotic adjustment in S. chilense, accounting respectively for 47 and 60% of osmotic potential. In contrast the contributions of proline and soluble sugars remained marginal for the two species although salt-induced accumulation of proline was higher in S. lycopersicum than in S. chilense . Both species also differed for their hormonal status under salinity and concentrations of most hormonal compounds were higher in S. chilense than in S. lycopersicum . Interestingly, salicylic acid, ethylene and cytokinins were positively correlated with osmotic potential in S. chilense under salinity while these hormones were negatively correlated with osmotic adjustment in S. lycopersicum . Our results suggested that the capacity to use inorganic ions as osmotica may improve salt resistance in S.chilense and that phytohormones could be involved in this process.